Web-Based Competency Test Information System with Automated Scoring Using the Waterfall Method - Burhanuddin Damanik; Sadarmanis Halawa (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
The implementation of competency tests in vocational high schools (SMK) is still largely conducted manually, leading to several issues such as delays in score processing, data recording errors, and inefficiencies in managing examination records. This study aims to design and develop a web-based competency test information system using the Waterfall method to improve efficiency, accuracy, and transparency in the examination process. The system was developed using PHP, MySQL, HTML, CSS, and JavaScript, incorporating six main features: user login, participant registration, question management, online examination, automatic scoring, and result reporting. System evaluation was conducted using Black Box Testing to assess functional performance and the System Usability Scale (SUS) to measure user satisfaction. The results show that all system features operated successfully with a functional success rate of 100% across all test scenarios, indicating high system reliability. In addition, usability evaluation involving 30 respondents, consisting of 20 students and 10 teachers, resulted in an average SUS score of 92, which falls into the “excellent” category. The system also significantly improves efficiency by reducing result processing time from 2–3 days to real-time processing, while minimizing data entry errors. Therefore, the developed system not only improves the efficiency and accuracy of competency test implementation but also provides a reliable and user-friendly solution, contributing to the development of educational information systems based on user experience.